“Denomination Doesn’t Matter”? A Proposal for a Receptive Ecumenical Missiology from a Theological Action Research Project on Methodists and Catholics Engaging Together in Social Action - Butler, James (Ecclesial practices, 2023)
In ecumenical social action and mission it is common to hear phrases like, ‘denomination doesn’t matter’, and ‘we are all just Christians’. This reflects a wider tension with modern ecumenism between doctrinal and practice-based approaches to ecumenism. In this theological action research project on Methodists and Catholics engaging together in social action many espoused this pragmatic approach to action over ecclesial tradition. However, in practice they engaged with the complexities of ecumenical life and ecclesial tradition, many in significant ways. Drawing on the themes of receptivity, identity and practical wisdom seen in their practice and their understanding of ecumenism as something which is ‘lived’ rather than ‘done’, I offer a receptive ecumenical missiology. This ecumenical missiology, based in a pneumatological receptivity, offers an integrated way forward, overcoming many of the tensions between practice, mission and doctrine felt within modern ecumenism.